A case of acute myelogenous leukaemia characterised by the BCR-FGFR1 translocation. (20th March 2013) - Matikas, Alexios; Tzannou, Ifigeneia; Oikonomopoulou, Dimitra; Bakiri, Maria
Abstract : The 8p11 myeloproliferative syndrome is a rare atypical disorder defined by the presence of rearrangements between the fibroblast growth factor receptor 1 (FGFR1) and 1 of 13 partner genes described to date, including the BCR gene on chromosome 22. The disease characterised by the BCR-FGFR1 fusion gene has distinct biological and clinical features, with significant diversity among the published cases. We report a case of BCR-FGFR1 disease which was presented as acute myeloid leukaemia with an aggressive clinical course and we review all the adult cases published in the literature.